The utilization of red mud waste as industrial honeycomb catalyst for selective catalytic reduction of NO. Issue 11 (13th November 2019) - Huangfu, Lin; Abubakar, Abdullahi; Li, Changming; Li, Yunjia; Wang, Chao; Yu, Jian; Gao, Shiqiu
Abstract : As a new way for the high-value utilization of red mud (RM) waste, we proposed an improved approach to prepare the RM-based sludge/powder via the sulfuric acid hydrothermal dissolution and NH3 aqueous precipitation route and then the RM-based industrial-sized honeycomb (150 × 150 × 600 mm) was successfully produced by the extrusion moulding method in pilot scale. The synthesized RM-based powdery/honeycomb catalyst exhibited more than 80% deNO x activity and good durability of H2 O and SO2 above 350°C. But the decline of NO conversion was also observed above 350°C, which was confirmed to result from the increased oxygenation of NH3 at high temperature. To improve the NO conversion at high temperature, NH3 was shunted and injected into the catalyst bed at two different places (entrance and centre) to facilitate its uniform distribution, which relieved the oxidation of NH3 and increased deNO x efficiency with 98% NO conversion at 400°C. This work explored the industrial application feasibility for the RM-based honeycomb catalyst as well as the possible solution to decrease the oxygenation of NH3 at high temperature, which presented a valuable reference for the further pilot tests of RM catalyst in industry.